In silico discovering relationship between bacteriophages and antimicrobial resistance - Maya Zhelyazkova; Roumyana Yordanova; Iliyan Mihaylov; Stefan Tsonev; Dimitar Vassilev (Biotechnology & Biotechnological Equipment)
Bacteriophages and their potential contribution to antimicrobial resistance (AMR) have attracted growing attention in the context of medicine and pharmaceutics. A major objective of the CAMDA challenge is to acquire more knowledge about the relationship between viruses, their hosts and AMR genes in determining if AMR indeed can spread through phages. This study is focused on exploring the relationship and possible dependencies between bacteriophages and AMR based on the data collected from urban environments all over the world. The samples in the data are classified into two categories: high and low, according to the observed levels of AMR genes. The approach used in our analyses consists of several different methods which assess the differential abundance of phages, their diversity across samples, the impact on AMR categories and associations with AMR genes. The relationship between phages, their hosts and AMR is also explored by a Bayesian spatial model, using the AMR category (low vs high) as a factor. We found a higher relative risk for phages known to infect Staphylococcus aureus alone or both S. aureus and Acinetobacter baumannii in the high AMR group, which implies that these phages may have a role in the dissemination of antimicrobial genes.